MICROSURGICAL MANAGEMENT OF LOW-GRADE SPINAL CORD ASTROCYTOMA IN ADULTS: A PERSONAL CASE SERIES REPORT AND BRIEF LITERATURE REVIEW - Pojskić, Mirza (Acta Clin Croat, 2020)
Astrocytoma is the second most common intramedullary tumor of predominantly low-grade malignancy in adult patients. Adult astrocytomas have better-quality prognosis compared with astrocytomas in children. Although a standardized surgical management protocol for spinal cord glioma is currently unavailable, surgery of low-grade astrocytoma should be aimed at gross total resection to preserve neurological function and to improve the outcome. Herein, we present a personal case series of four consecutive adult spinal cord astrocytoma patients who were operated on during the last few years. Tumor resection was performed in all patients utilizing microsurgical technique and intraoperative neurophysiologic monitoring. We also provide a literature review of the treatment of intramedullary astrocytoma in adults and discuss contemporary surgical management and prognosis.